#TITLE_ALTERNATIVE# - Hartanto Kimiady (NIM. 23300024), Tandy
Abstract: Low frequency noise and room temperature fluctuation at the dc voltage standard system influence do voltage stability which then degrade the accuracy and uncertainty on the standard value. Therefore noise characterization of the dc voltage standard system and temperature characterization of the do electronics standard cell are very important in the design optimization for an accurate and stable de voltage standard system. The objective of the study was to finely identificate noise characteristics and to obtain noise level at low frequency of the dc voltage standard system, use two-sample Allan variance statistic method (in time domain) and power spectral density analysis (in frequency domain). Also to observe the temperature influence on the output voltage characteristic of the do electronics standard cell. The noise characterization of the dc voltage standard system namely: do standard cell, scanner, nanovoltnieter, and wiring were performed by using two methods each two-sample Allan variance (statistic) and power spectral density (fast Fourier transform). From the analysis (characterization) were found the noise floor level of the do electronics standard cell (22.24 nl' is higher than its chemical do standard cell /Weston cell (8.04 nV). For the output voltage characterization of the electronics standard cell Cropico 1.018 volt as temperature function was used thermo element temperature controller to adjust the aluminium box temperature of the electronics standard cell from 20 to 34 °C. Temperature characteristics of the dc electronics standard cell was found fit to the temperature dependence:Vout= 1.018 803 25 V + (0.425.T - 0.0295.T<supp>2)µV with maximum curve fitting error 0.65 µV The analysis of the influenced temperature noise shows a condition, which has low noise floor level, when the box temperature approximately homogen.